Psychometric properties of the 12-item Stroke-Specific Quality of Life Scale among stroke survivors in Hong Kong - Ted C. T. Fong; Temmy L. T. Lo; Rainbow T. H. Ho (Scientific Reports, 2023)
Abstract The present study examined the psychometric properties of the 12-item Stroke-Specific Quality of Life Scale (SSQOL-12) in 184 stroke survivors in Hong Kong. The participants completed a self-report questionnaire including the SSQOL-12, SF-12 health survey, and validating variables at baseline and 148 stroke survivors completed SSQOL-12 two months later. Confirmatory factor analysis investigated the construct validity, reliability, and measurement invariance of SSQOL-12 across two months. Concurrent, convergent, and divergent validity was examined with respect to SF-12, hope, self-esteem, functional disability, anxiety, and depression. The original 2-factor model did not reveal a superior fit over the 1-factor model and a modified 1-factor model provided an acceptable fit to the data in both waves. The SSQOL-12 factor displayed substantial factor loadings (λ = 0.40–0.87), good internal consistency (Ω = 0.88), temporal stability (r = 0.70), and scalar measurement invariance across time. Stroke-specific quality of life was significantly associated with higher levels of SF-12, hope, and self-esteem and lower levels of functional disability, anxiety, and depression. Most correlations remained significant after controlling for demographic covariates and SF-12. The present findings offered empirical support for the validity and reliability of the unidimensional structure for SSQOL-12 as a measure of stroke-specific quality of life among stroke survivors.